How "Alone" are Lone-Actors? Exploring the Ideological, Signaling, and Support Networks of Lone-Actor Terrorists. (2nd July 2020) - Hofmann, David C.
Abstract: Conventional knowledge and early academic work on lone-actor terrorists has popularized the concept that they radicalize, operate, plan, and execute plots in relative anonymity, with little connection to formal or more organized terrorist groups and networks. However, recent scholarship has increasingly challenged the notion of the "loneliness" of lone-actors. In order to further empirically test this notion, this article uses social network analysis to examine the ideological, signaling, and support networks of two case studies of lone-actors during the twenty-four months prior to the commission of their first act of terrorist violence.